Pembinaan Prestasi Sekolah Sepak Bola - Achmad Afandi; Winarno Winarno; Yuskhil Mushofi; Alfian yahya; Adi Sucipto; Ahmad Lani; Titik Purwati; Chindy hanggara Rosa Indah (Lembaga Pengembangan Kinerja Dosen, 2024)
Until now, SSB Purwodadi is very burdensome for its owners and administrators because SSB still depends on the owner for its operational costs from SSB students. SSB Purwodadi is located in Purwodadi sub-district, located in Pasuruan district. This Ssb was founded from the awareness of the community around the location and football coaches who want to encourage the realization of positive habit activities in sports, especially football. In children's football, students who were initially physically and healthless through football became physically strong, physically fit, and their confidence and cooperation could be established. As well as spiritual values and honesty will emerge. And for trainers after this service is held, they can train and teach well, correctly and professionally, of course. And hopefully football seeds can be born with a good football magazine and a good training program and there is valid data in the football learning process. And from the student and coach questionnaire survey, we can find out that after doing service, there is a score of 22 out of a total score of 25 scores from 5 questions, which indicates that there is 88% of the total of 100 percent of the overall score and this service has a good impact Keywords: football school, curriculum, evaluation.